Modern approaches in fuzzy sets, intuitionistic fuzzy sets, generalized nets and related topics. Volume II: Applications * Assessment finance approach from the glance of a generalized net model, implemented in a structural unit of a financial institution - Atanassova, Vassia; Doukovska, Lyubka; Shahpazov, George (Instytut Badań Systemowych. Polska Akademia Nauk, 2014)
In the present paper, an application of the apparatus of generalized nets is proposed for modeling of the mechanism of financial support of small and medium-sized enterprises (SME). The model aspects of internal financial structural units functionalities are reflected, and it is offered how the concept of the generalized nets (GN) can be applied to the process of evaluating creditworthiness of the SMEs applications for bank loans, from the banks perspective.
[3], 93-102 stron ; 21 cm
Bibliografia s. 101-102

Modern approaches in fuzzy sets, intuitionistic fuzzy sets, generalized nets and related topics. Volume II: Applications * Generalized net model of internal structural unit functionality, focused on sme financing - Atanassov, Krassimir Todorov (1954– ); Doukovska, Lyubka; Shahpazov, George (Instytut Badań Systemowych. Polska Akademia Nauk, 2014)
In this paper is provided an analysis using the Generalized Nets (GN). They are used as a tool for modelling of different processes in industry, medicine, different branches of artificial intelligence, etc. In the present paper is discussed an application of the GN apparatus for assistive technology and the advantages of using such model, for describing the financial support mechanism of the small and medium-sized enterprises (SMEs). It is proposed an original GN model of internal structural bank unit functionality. The advantage of this approach is in modelling the inherent aspects of parallelism and concurrency between agents in a situation of competition.
[3], 83-92 stron ; 21 cm
Bibliografia s. 92